Public Deliberation and Co-Production in the Political and Electoral Arena: A Citizens’ Jury Approach - Greg Munno; Tina Nabatchi (Journal of Deliberative Democracy, 2014)
This study presents an empirical evaluation of the co-production of a “Statement to the Candidates” and a “Voters Guide” for a key U.S. Congressional race. Citizens produced these materials during an intensive process called “Reclaim November Ohio,” which used the Citizen Jury method of public deliberation. We use a series of pre- and post-test surveys to evaluate this unique application of co-production. Specifically, we assess whether this deliberative approach to co-production in the political and electoral arena improved participants’ perceptions of politics and government and made citizens more interested in and knowledgeable about policy issues. We also assess whether participants believed the Reclaim November Ohio process would help the candidates better understand citizens’ concerns and whether participants were satisfied with the event. The results suggest that co-production in the political and electoral arena can have positive effects on citizens’ agency, voice, and perceptions of politics and government. The results are mixed for both the perceived influence of the event and issue interest and knowledge. Nevertheless, participants were extremely satisfied with the event and its various components.